Profitability and optimal debt ratio of the automobiles and parts sector in the Euro area - Charalampos Basdekis; Apostolos G. Christopoulos; Ioannis Katsampoxakis; Alexandros Lyras (Journal of Capital Markets Studies (JCMS), 2020)
Purpose The goal of this paper is twofold: to assess the influence of specific corporate and market features on automobiles and parts sector's profitability in Euro area and to identify this particular sector's optimum debt level. Design/methodology/approach For the paper's purposes, the authors applied a panel data analysis on an annual basis for the period 2005-2017. Findings There is a strong statistical significance of debt ratio, growth domestic product per capita growth, E.C.'s economic sentiment index (ESI), the European Central Bank key interest rate and the Euro area crisis on sector's profitability, while weak statistical significance appears to emerge for the firm's size. Moreover, the authors find average 14.4% profitability for the entire sector of the Euro area, without significant fluctuations among firms and/or during the examined time period. Another interesting finding of this study is that results are consistent with the theory of Modigliani Miller that financial leverage at a "low" level is beneficial for the firm, but beyond a turning point, it becomes counterproductive. This turning point for the automobiles and parts sector in Euro area has been computed at 47.3%. Originality/value The paper focuses on issues of profitability, capital structure and optimal debt ratio of an important sector of the economy, the automotive sector. As regards the Euro area automotive sector, it is a dynamic sector with a significant multiplier effect for the European economy as it is strongly correlated with other industrial sectors as chemicals, steel, textiles, information technology and so forth, having an outstanding multiplier effect on the economy.
Keywords: 330; Profitability; Financial leverage; Size; GDP per Capita; Economic sentiment index; Optimal debtratio; Economic crisis; Automobile and parts sector